ANALISIS PENGARUH PERSEPSI HARGA, PROMOSI, DESAIN PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC (Studi Pada Yamaha Mataram Sakti Semarang) - Pahlevi, Anzaruddin Septian; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2017)
The background of the research is the increasing number of matic motorcycle in Indonesia with the own unique features and characteristic. This phenomeon is related to incresing demand of practical vehicle that can cater’s needs of high mobility. This research aims to analyze price perception (X1), promotion (X2), product design (X3), and product qualit (X4) upon purchasing decision (Y) of matic motorcycle in Yamaha Mataram Sakti Semarang.Population used in this research is consumer bought used mtorcycle in Yamaha Mataram Sakti Motor Semarang. Total sample used is 100 respondents. Sampling tehcnique used on this research is purposive sampling. Data used is gathered questionaire, analysis used in this research is multiple regression.The result is, Y = 0,202X1 + 0,212X2 + 0,245X3 + 0,368X4. Independent variable which is very influential concerning to dependent variable is quality product (0,368) followed by product design variable (0,245), promotion (0,212), and the last is price perception variable (0,202). The result prove that all of independent variables (price perception, promotion, product design, product quality) have positive influence toward dependent variables that is purchasing decision.